Evaluation of anti-inflammatory potential of hydro-alcoholic extract of root of Salacia oblonga - Mayank Mahore; Sandeep Jain (The Bioscan, 2026)
In this work, hydroalcholic extract of Salacia oblonga was assessed for it anti- inflammatory action using Carrageenan induced paw edema method in rats.